2016
DOI: 10.18632/oncotarget.12964
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lung cancer in Parkinson's disease

Abstract: Recently, growing evidence has revealed the significant association between Parkinson's disease (PD) and cancer. However, controversy still exists concerning the association between PD and lung cancer. A comprehensive article search for relevant studies published was performed using the following online databases: PubMed, Web of Science and Embase up to August 31, 2016. The pooled risk ratio (RR) and their 95 % confidence intervals (CI) were calculated using the method of inverse variance with the random-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…4 Therefore, we evaluated tobacco smoking and the 2 cancers with very high (>80%) attributable risk for smoking (lung cancer and laryngeal cancer). [11][12][13] We made a dichotomous ever vs never smoking variable with 4 codes specific to tobacco use: history of smoking (ICD-9-CM V15.82), nicotine dependence (ICD-9-CM 305.1), and 2 procedure codes for tobacco cessation counseling (99406 and 99407). We also made a more comprehensive ever smoking variable.…”
Section: Ascertainment Of Other Medical Conditionsmentioning
confidence: 99%
“…4 Therefore, we evaluated tobacco smoking and the 2 cancers with very high (>80%) attributable risk for smoking (lung cancer and laryngeal cancer). [11][12][13] We made a dichotomous ever vs never smoking variable with 4 codes specific to tobacco use: history of smoking (ICD-9-CM V15.82), nicotine dependence (ICD-9-CM 305.1), and 2 procedure codes for tobacco cessation counseling (99406 and 99407). We also made a more comprehensive ever smoking variable.…”
Section: Ascertainment Of Other Medical Conditionsmentioning
confidence: 99%
“…Interestingly, a large number of epidemiological studies have shown a significant reduction in the risk of cancer in patients with Parkinson’s disease (PD) [ 4 ]. A meta-analysis of 15 studies, involving 348,780 patients with PD, showed a significant negative correlation between PD and lung cancer risk (RR: 0.53, 95%CI: 0.41–0.70, P < 0.001) [ 5 ]. Both PD and lung cancer are multifactorial disorders involving genes and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, DAs doses used for this condition are typically higher—as much as six times higher—when compared to those used in RLS 42 . As aforementioned, patients with PD were excluded from our main analysis because PD itself has been associated with a lower risk of developing different types of cancer 27–29 . However, we evaluated the effect of including patients diagnosed with PD after cohort entry as a sensitivity analysis; after inclusion of these patients, results did not vary, suggesting that our results are robust across study populations.…”
Section: Discussionmentioning
confidence: 99%